Effectiveness of Using Android-Based Learning Media in Increasing Understanding and Basic Techniques of Student Basketball Games - Iman Rubiana; Budi Indrawan; Arief Abdul Malik (Universitas PGRI Palembang, 2023)
This research is a follow-up study to test the effectiveness of learning media based on android applications that have been developed and validated by experts in previous studies. The Penjas Unsil Basketball Guige (PUBbG) application has been successfully created and validated by experts with good criteria,, which can already be tested for implementation on students, and research articles have been published in the JUARA Sinta 3 Journal. Therefore, in this study, the researcher attempted to investigate the effect of using an Android application-based learning media called Penjas Unsil Basketball Guide (PUBbG) in increasing students' understanding and basic techniques of playing basketball. As an illustration of the information in the Unsil Basketball Guide (PUBbG) Penjas application which includes a video tutorial on basic techniques that must be mastered by students at a minimum, along with a narrative text module which supports the video. The research method used is an experimental method with a pretest-posttest design to determine the effect of applying products made to increasing understanding and basic basketball techniques. Participants in this study were students of Physical Education at Siliwangi University. The instrument used was a student comprehension test with the Basketball Common Content Knowledge test and the Basic Basketball Skills Technique Test. Furthermore, the data analysis technique used is the t test to determine the effectiveness of the product used by testing the differences in pre-test and post-test results after implementing android application products and comparing them with the control group. The results showed that even though the two groups both showed an increase, only the understanding of students who had a significant difference with the experimental group had more impact than the control group. Whereas in basic technical skills, there was no significant difference between the two groups.